Estimation of Oxidant and Anti-oxidant Status in Patients with Changeful Heart Discomfort and Myocardiac Breach of Diwaniya-Iraq - AL-Mohammad, Hussein Mahdi K; hussan, Falah; Habeeb, Thuria Amar (Cardiology and Cardiovascular Medicine, 2019)
The present study aimed investigated the relationship between level oxidate and Anti-oxidant of patients with changeful heart discomfort pectoris, myocardiac breach and identify role oxidate in develop disease of individual province of diwaniya-iraq. The study of patients who are divided into three category (A) included 45 patients changeful heart discomfort pectoris in different age, category (B) included 45 patients with acute myocardiac breach at different age and category 45 (C) as control. The results demonstrate show a significant decrease (p ≥ 0. 05) in vitamin E, C, glutathion peroxidas and Glutathione (GSH) but the reverse was significant increase (p ≤ 0. 05) caeruloplasmin (ferroxidase enzyme), and Malondialdehyde (MDA) of individual changeful heart discomfort pectoris and myocardiac breach. The conclusion of study the negative role of high free radical was subsisted heart disorder progress. The acute myocardiac breach work reduction of oxygen delivery to myocardium lead generation of reactive oxygen groups that play an effective role in the pathogenesis heart disorder.